Elaboration of Aromatic Candles with used oil as a strategy for the prevention of contamination in water sources - Pedroza Fontalvo, María Fernanda
By making aromatic candles with recycled oil, you will be contributing to the reduction of CO2 emissions, since for each recycled ton the emission of three tons of carbon dioxide is saved, which is why many companies today are dedicated to the collection and treatment of these to generate new products, mentioning that the people who dispose of the oil through the domestic pipes do so without knowing that it can be reused to give it different uses, for which the realization of aromatic candles made with used oils is proposed. which will be obtained by the community.